2023
DOI: 10.1136/dtb.2022.000066
|View full text |Cite
|
Sign up to set email alerts
|

Managing drugs with anticholinergic activity

Delia Bishara

Abstract: Over the past two decades, considerable data have emerged on an association between drugs with anticholinergic activity and serious adverse effects in older people. Well-recognised anticholinergic adverse effects include dry mouth, blurred vision, constipation and urinary retention. Of particular concern is the potential impact on cognitive function with several studies showing that long-term use of medicines with anticholinergic activity is associated with worsening of cognitive function, increased incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Although the benefits of using antipsychotics may outweigh the risks for managing specific psychiatric symptoms, many studies that have found a causal relationship between antipsychotics and delirium or no therapeutic effect. Clozapine is contraindicated for delirium treatment due to its significant anticholinergic effects, which can exacerbate cognitive impairment and cause delirium [ 69 ]. Similarly, sustained-release olanzapine is potentially harmful for managing delirium because of its long-acting nature and risk of causing delirium [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the benefits of using antipsychotics may outweigh the risks for managing specific psychiatric symptoms, many studies that have found a causal relationship between antipsychotics and delirium or no therapeutic effect. Clozapine is contraindicated for delirium treatment due to its significant anticholinergic effects, which can exacerbate cognitive impairment and cause delirium [ 69 ]. Similarly, sustained-release olanzapine is potentially harmful for managing delirium because of its long-acting nature and risk of causing delirium [ 70 ].…”
Section: Discussionmentioning
confidence: 99%